Novel diagnostic test for the detection of Mycobacterium tuberculosis and its resistance to rifampicin, isoniazid, and fluoroquinolones directly in sputum samples - Ramasubban, Gayathri; Michael, Joy Sarojini; Gupta, Richa; Channamaneni, Kavyasri; Krishnan, Dhanabagyam; Chandran, Dev; Hoffner, Sven; Asalapuram, Pavankumar (Frontiers in Tuberculosis, 2025)
IntroductionRapid identification of tuberculosis (TB) and its drug resistance is crucial for starting effective treatment promptly and preventing the spread of resistant Mycobacterium tuberculosis (MTB) strains. Expanding the use of existing and new rapid molecular diagnostic tests is urgently needed to combat the rising threat of TB, multidrug-resistant TB (MDR-TB), and pre-extensively drug resistant TB (pre-XDR-TB). The mfloDx™ diagnostic platform was developed to provide efficient, accurate, and accessible TB diagnostics. This study evaluates the performance of the mfloDx™ pre-XDR-TB test for detecting TB and drug resistance against MGIT culture and drug susceptibility testing (DST).MethodologyWe have evaluated the performance of mfloDx™ pre-XDR-TB test on 731 sputum samples received from a tertiary care center in India. This study compares the analytical and clinical efficiency of mfloDx™ pre-XDR-TB test against the MGIT culture for M. tuberculosis complex (MTC) and MGIT-DST for rifampicin (RIF), isoniazid (INH), and fluoroquinolone (FQ) resistance. The clinical sensitivity and specificity were calculated for TB and drug-resistance detection using MedCalc statistical software.ResultsThe mfloDx™ pre-XDR-TB test showed 86.2% of sensitivity and 82.0% of specificity for MTC detection against MGIT culture. For drug resistance detection, sensitivity and specificity were found to be 98.2% and 99.7% for RIF, 86.2% and 99.2% for INH, and 93.3% and 100% for FQ, respectively, while the Indeterminate rates were 1.1% for RIF, 2.0% for INH, and <1% for FQ. The mfloDx™ pre-XDR-TB test's high specificity minimized false positives, which is essential for preventing unnecessary treatments, while rapid results offered a significant advantage over conventional methods.ConclusionThe mfloDx™ pre-XDR-TB test efficiently provides a reliable, rapid and specific diagnostic results for TB and its drug resistance detection. While it shows potential for inclusion in the clinical diagnostic workflows, especially in high-burden areas, further optimization are required to enhance its sensitivity. Nonetheless, the test offers significant advantages for the prompt management of drug-resistant TB in resource-limited settings.